Become an octopus organization: How your company can adapt to a complex world. - Werner, Jana and Le-Brun, Phil (Harvard Business Review)
As companies pour trillions into transformation efforts, few see lasting results. That$1 (Bs because most organizations approach change like machines$1 (Brigidly, predictably, and from the top down, argue Amazon Web Services enterprise strategists Jana Werner and Phil Le-Brun. In this article, adapted from their forthcoming book The Octopus Organization (Harvard Business Review Press, 2025), the authors offer a radically different paradigm: the Octopus Org. Modeled after one of nature$1 (Bs most adaptive and intelligent creatures, the Octopus Org distributes decision-making, senses change in real time, and continually adapts. Unlike (3z(BTin Man(3y (Borganizations that view business as complicated but controllable, Octopus Orgs recognize the truly complex nature of today$1 (Bs world, which is nonlinear, uncertain, and constantly evolving. The key to thriving in it is to change antipatterns$1 (Bdeep-seated habits that compromise clarity, ownership, and curiosity. The shift to this model doesn$1 (Bt unfold in predictable, scalable phases. It happens organically, as local teams solve meaningful problems and share what works. The prize? Greater adaptability, deeper engagement, stronger innovation, and, ultimately, lasting advantage.-Reproduced s